Production, characterization, and cytotoxicity of calcium phosphate ceramics derived from the bone of meagre fish,Argyrosomus regius - Aydin, Gulsum; Terzioğlu, Pınar; Öğüt, Hamdi; Kalemtaş, Ayşe (Springer, 2021)
Hydroxyapatite ceramics derived from organic materials have similar physical properties and chemical content to stoichiometric hydroxyapatite ceramics produced via synthetic routes. The focus of the current study is to produce hydroxyapatite ceramics from meagre fish bones via calcination method. To the knowledge of the authors, this is the first report in which the meagre fish bones are used to produce hydroxyapatite. The effect of calcination temperature on the phase content, chemical composition, microstructure, and cytotoxic properties of hydroxyapatite ceramics produced from the bones of meagre fish,Argyrosomus regius, was investigated. Thermogravimetric-differential thermal analysis of the raw fish bones was performed over a temperature range of 20-1100 degrees C under air atmosphere with a heating rate of 10 degrees C/min. The total mass loss at this temperature range was about 59% for the fish bone. Thermal analysis of the sample exhibited a three major weight change stage. Calcination was performed in an air atmosphere at different calcination temperatures ranging from 800 to 1100 degrees C for 1 h. XRD analyses of the calcined fish bones revealed that the hydroxyapatite and whitlockite phases were formed at all calcination temperatures. Significantly marked alterations were observed at the microstructure of the samples depending on the calcination temperature. Scanning electron microscopy investigations revealed that nanocrystalline hydroxyapatite particles were achieved at 800 degrees C. As the calcination temperature was increased, particle size of the calcium phosphate phase was also increased and reached to approximately 1 mu m for the sample calcined at 1100 degrees C. Cytotoxicity evaluation of the hydroxyapatite carried out using XTT assay demonstrated that the materials are non-cytotoxic at concentrations up to 100 mg/ml.
Keywords: Meagre fish bone; Calcination; Calcium phosphate ceramics; Cytotoxicity